2019
DOI: 10.3390/f10070575
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Species Distribution Models Based on Available Climate Change Data: A Case Study in the Azorean Forest

Abstract: Climate change is gaining attention as a major threat to biodiversity. It is expected to further expand the risk of plant invasion through ecosystem disturbance. Particularly, island ecosystems are under pressure, and climate change may threaten forest-dependent species. However, scientific and societal unknowns make it difficult to predict how climate change and biological invasions will affect species interactions and ecosystem processes. The purpose of this study was to identify possible limitations when ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 128 publications
1
16
0
1
Order By: Relevance
“…The structure of PF and EW was mainly influenced by the dominant species Cryptomeria japonica and Pittosporum undulatum, with the highest basal area and tree density. The structural dominance of P. undulatum in exotic woodland confirms the potential of this species to originate almost pure stands[40][41][42]69,70,[85][86][87].…”
supporting
confidence: 57%
See 1 more Smart Citation
“…The structure of PF and EW was mainly influenced by the dominant species Cryptomeria japonica and Pittosporum undulatum, with the highest basal area and tree density. The structural dominance of P. undulatum in exotic woodland confirms the potential of this species to originate almost pure stands[40][41][42]69,70,[85][86][87].…”
supporting
confidence: 57%
“…Higher values of precipitation and lower values of temperature were found for NF, and an inverse situation for EW, since the remaining NF are mostly found at high elevation sites, at sloped terrain [51], while EW is generally found at low elevation and at places with higher temperatures [69][70][71][72].…”
Section: Discussionmentioning
confidence: 92%
“…Akpoti et al used BRT, GLM, MAXNT and RF algorithms to predict rice production suitability and the results showed that RF has better generalizability 28 . Silva et al found the highest model quality for the RF and GAM algorithms when assessing the limitations of different species distribution models using the Azorean Forest as an example 29 . The RF is an ensemble machine-learning model that could handle data with multi-dimensional, non-linear relationships, high-order correlations, and missing values 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The survey addressed dairy farmers of São Miguel Island (Azores). Located in the middle of the Atlantic Ocean, the Azores is an archipelago with 9 islands, with mild temperatures (minimum and maximum temperature: 12.0–18.4 °C, respectively), humidity (minimum and maximal relative humidity: 89.0–97.4%) [ 26 , 27 ], and an abundant rainfall climate with precipitation of 960.6 ± 201 mm per year, with 75% of the precipitation falling between October and March [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%